2021
DOI: 10.1088/1361-6668/ac04ba
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional peridynamic modeling of crack initiation and propagation in bulk superconductor during field cooling magnetization

Abstract: Bulk high-temperature superconductors exhibit outstanding electromagnetic properties and are capable of trapping very large magnetic fields. However, bulk superconductors are subjected to a large Lorentz force during field cooling magnetization (FCM), which can cause crack initiation and propagation. Superconducting performance is then limited by the damage to the bulk. In this paper, we study the mechanical behavior and brittle damage of a three-dimensional (3D) bulk GdBCO superconductor during FCM. Firstly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Subsequently, according to strain measurement results, Takahashi [7] and Namba [17] constructed 2D and 3D numerical models to analyze the fracture behavior of HTS bulk and further considered the effect of the real structure of the mechanical support apparatus. Recently, apart from the FEM, the extended finite element method (XFEM) [18,19], peridynamics (PDs) [20,21], and phase-field method [22,23], the theories of fracture mechanics, were also gradually employed in the structural failure analysis of bulk materials caused by crack propagation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, according to strain measurement results, Takahashi [7] and Namba [17] constructed 2D and 3D numerical models to analyze the fracture behavior of HTS bulk and further considered the effect of the real structure of the mechanical support apparatus. Recently, apart from the FEM, the extended finite element method (XFEM) [18,19], peridynamics (PDs) [20,21], and phase-field method [22,23], the theories of fracture mechanics, were also gradually employed in the structural failure analysis of bulk materials caused by crack propagation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, based on the r-z plane spatial J c inhomogeneity method, the electromagnetic-mechanical coupling behavior of many high-field bulk material application devices, such as high-gradient trapped field magnet (HG-TFM) [48], staggered-array bulk HTS undulator [30,49], nuclear magnetic resonance (NMR) spectrometer [50] and a magnetic resonance imaging (MRI) apparatus [51], and others, can be simulated more precisely. Many complex HTS bulk material structure failure simulation modes, such as fracture, crack initiation, and propagation [19,21], may also achieve better agreement with experimental phenomena.…”
mentioning
confidence: 99%
“…The magnetic-thermal characteristics and mechanical stress of an REBCO superconducting bulk material with an inhomogeneous critical current density during PFM were analyzed by Wu et al [62] and Hirano et al [63]. In addition, cracks in the bulk can propagate under complicated electromagnetic and mechanical loadings [64][65][66]. The coupled magnetic-thermal model and phase-field fracture model were proposed to simulate the flux jump and mechanical failure behaviors of bulk superconductors during PFM [67].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, thermomagnetic instability is coupled with mechanical failure. In the past few years, many researchers have contributed to the investigation into the mechanical stresses [40,41] and the fracture/damage [42][43][44][45] evolution within bulk superconductorsduring magnetization. However, few works [46][47][48] have been reported that investigate the fully coupled thermomagnetic-mechanical instability behavior in bulk superconductors.…”
Section: Introductionmentioning
confidence: 99%